Heparin Cofactor II Deficiency in Patients Infected with the Human Immunodeficiency Virus - Toulon, P; Lamine, M; Ledjev, I; Guez, T; Holleman, M E; Sereni, D; Sicard, D (Thrombosis and Haemostasis, 1993)
In human plasma, heparin cofactor II (HCII) is a thrombin inhibitor, whose deficiency has been reported to be associated with recurrent thrombosis. The finding of two cases of low plasma HCII activity in two patients infected with the human immunodeficiency virus (HIV) led us to investigate this coagulation inhibitor in the plasma of a larger population of HIV-infected patients. The mean plasma HCII activity was significantly lower in 96 HIV-infected patients than in 96 age- and sex-matched healthy individuals (0.75 ± 0.24 vs 0.99 ± 0.17 U/ml, p <0.0001). HCII antigen concentration was decreased to the same extent as the activity. The proportion of subjects with HCII deficiency was significantly higher in the HIV-infected group than in healthy individuals (38.5% vs 2.1%). In addition, HCII was significantly lower in AIDS patients than in other HIV-infected patients, classified according to the Centers for Disease Control (CDC) on the basis of an absolute number of circulating CD4+ lymphocytes below 200 x 106/1. The link between HCII and immunodeficiency is further suggested by significant correlations between HCII activity and both the absolute number of CD4+ lymphocytes and the CD4+ to CD8+ lymphocyte ratio. Nevertheless, the mean HCII level was not different in the various groups of patients classified according to clinical criteria, except in CDC IVD patients in whom HCII levels were significantly lower. In addition, no correlation could be demonstrated between HCII and protein S activities, another coagulation inhibitor whose plasma level was also found to be decreased in HIV-infected patients. A similar prevalence of HCII deficiency was also found in a small series of 7 HIV-infected patients who developed thrombotic episodes, an unusual complication of the infection. This suggests that, in HIV-infected patients, HCII deficiency is not in itself the causative factor for the development of thrombosis.